INTEGRATION OF LANDSCAPE ARCHITECTURE PRINCIPLES INTO THE GREENING AND PLANNING OF URBAN GARDEN-PARK TERRITORIES - Nahorna, Svitlana; Blyk, Tetiana (Theory and practice of design, 2025)
Purpose. The purpose of the study is to substantiate and practically implement the integration of landscape architecture principles into the process of greening and planning garden and park areas of the urban environment, taking into account ecological, aesthetic, and socio-recreational requirements. The main focus is on the formation of sustainable spatial structures capable of improving the quality of the urban environment and the level of comfort for its residents. Methodology. The research employed methods of spatial analysis, field surveys, morphological analysis of plant communities, and visual-graphic modeling in the Figma environment to create conceptual design proposals. The theoretical basis consists of scientific works by Ukrainian and foreign authors devoted to the development of green infrastructure, principles of sustainable urban greening, and ecological-architectural planning. Results. As a result of the study, a concept for the spatial organization of the green area was developed using the example of Poltava State Agrarian University. Projects of multi-tiered plantings using ornamental shrubs and herbaceous plants were proposed and implemented, ensuring compositional harmony and ecosystem stability. During the reconstruction of the territory, the principles of ecological feasibility, landscape harmony, and functional interaction of different spatial elements were prioritized. The implementation of the projects made it possible to create a space that simultaneously performs recreational, sanitary-hygienic, and aesthetic functions. The use of plant species resistant to climatic conditions increased the adaptability of plantings and reduced the maintenance needs of the designed areas. The evaluation of the implemented solutions demonstrated a significant improvement in environmental quality. Thus, the developed concept confirmed the effectiveness of integrating ecological and design approaches into the spatial planning of green areas, which can serve as a model for the further development of similar objects. Scientific novelty. The sequence of applying landscape architecture principles in the greening process of urban areas has been substantiated, combining visual-compositional and ecological analysis. Practical relevance. As a result of the research, methodological principles were proposed for effectively combining architectural and design solutions with an emphasis on preserving natural ecosystems, which is an essential condition for the formation of sustainable urban systems.